Differential expression of parvalbumin in neonatal phencyclidine‐treated rats and socially isolated rats. (25th December 2012) - Kaalund, Sanne S.; Riise, Jesper; Broberg, Brian V.; Fabricius, Katrine; Karlsen, Anna S.; Secher, Thomas; Plath, Niels; Pakkenberg, Bente
Abstract Decreased parvalbumin expression is a hallmark of the pathophysiology of schizophrenia and has been associated with abnormal cognitive processing and decreased network specificity. It is not known whether this decrease is due to reduced expression of the parvalbumin protein or degeneration of parvalbumin‐positive interneurons (PV+ interneurons). In this study, we examined PV+ expression in two rat models of cognitive dysfunction in schizophrenia: the environmental social isolation (SI) and pharmacological neonatal phencyclidine (neoPCP) models. Using a stereological method, the optical fractionator, we counted neurons, PV+ interneurons, and glial cells in the medial prefrontal cortex (mPFC) and hippocampus (HPC). In addition, we quantified the mRNA level of parvalbumin in the mPFC. There was a statistically significant reduction in the number of PV+ interneurons (p = 0.021) and glial cells (p = 0.024) in the mPFC of neonatal phencyclidine rats, but not in SI rats. We observed no alterations in the total number of neurons, hippocampal PV+ interneurons, parvalbumin mRNA expression or volume of the mPFC or HPC in the two models. Thus, as the total number of neurons remains unchanged following phencyclidine (PCP) treatment, we suggest that the decreased number of counted PV+ interneurons represents a reduced parvalbumin protein expression below immunohistochemical detection limit rather than a true cell loss. Furthermore, these results indicate that the effect of neonatal PCP treatment is not limited to neuronal populations.